Tailoring the anisotropic (positive/zero/negative) thermal expansion in shape memory alloys through phase transformation and martensite (re)orientation. (1st July 2022) - Zhang, M.; Baxevanis, T.
Abstract: Recent experiments demonstrated that the macroscopic thermal expansion (TE) response of bulk shape memory alloys (SMAs) can be tailored via martensite variant texturing by taking advantage of the significant intrinsic TE anisotropy of the martensite lattice. Here, a description of the TE response of SMAs is proposed, which relies on the volume fraction of oriented (detwinned) martensite and the orientation direction tensor. The model is validated by comparing simulations against available experimental data on the positive/zero/negative TE of a polycrystalline NiTiPd SMA upon deformation processing and applied to track the TE evolution due to phase transformation and reorientation induced under nonproportional loading.